Screening compounds of Chinese medicinal herbs anti-Marek's disease virus. (July 2014) - Sun, Yaogui; Niu, Li; Song, Meiqin; Zhao, Xin; Sun, Na; He, Junping; Wu, Caihong; Jiang, Junbing; Bai, Yuansheng; Guo, Jianhua; Li, Hongquan
Abstract Context: Marek's disease (MD) seriously threatens the world poultry industry and has resulted in great economic losses. Chinese medicinal herbs are a rich source for lead compounds and drug candidates for antiviral treatments. Objective: To investigate the anti-MDV activity and mechanism of 20 compounds extracted from Chinese medicinal herbs. Materials and methods: Antiviral assay, time of addition experiments, and virucidal assay were performed on chicken embryo fibroblast cells. The 50% cytotoxic concentration and 50% effective concentration were determined and, accordingly, selectivity index and inhibition ratio were calculated. Results: Antiviral assay showed dipotassium glycyrrhizinate (DG) and sodium tanshinone IIA sulfonate (STS) exhibited significantly inhibitory activity against MDV in a dose-dependent manner. EC50 of DG and STS were 893.5 ± 36.99 µg/mL and 54.82 ± 2.99 µg/mL, and selective index (SI) were >3.36 and >9.12, respectively. Time of addition experiment and virucidal assay demonstrated DG inhibited viral replication in the full replication cycle and inactivated MDV particles in non-time-dependent manner, but STS interfered with the early stage of MDV replication and inactivated MDV particles in a time-dependent manner. Moreover, both DG and STS promoted apoptosis of cells infected by MDV. Discussion and conclusion: DG and STS have great potential for developing new anti-MDV drugs for clinic application.